Green Synthesis of Calcium/Iron-Layered Double Hydroxides-Sodium Alginate Nanoadsorbent as Reactive Barrier for Antibiotic Amoxicillin Removal from Groundwater - Marwa F. Abed; Ayad A. H. Faisal (Adsorption Science & Technology)
This work uses a new nanoadsorbent after chemically synthesis from chicken eggshell wastes for removing amoxicillin (AMX) from aqueous solution. This removal was examined as a time function, initial concentration of AMX, pH, agitation speed, and adsorbent dosage. The study achieved the optimum time for equilibration in (90) min, at pH=7 with an adsorbent dosage of 1.2 g. We applied many kinetic models to the sorption kinetic data where the pseudo-second-order model (R2=0.9924) was used to interpret the gained data at a rate constant K2 of (0.0077) g/(mg. min) at 200 rpm. Moreover, the adsorption calculated amount reached the experimentally required value and isotherm data best fitted the Langmuir model with R2 (≥0.9486) than the Freundlich model. The intraparticle diffusion model revealed a diffusion dependent process. The different functional sets on the calcium/iron-surface as a layered double hydroxide (Ca/Fe)-LDH were important in sorpting the selected antibiotic. Forming (Ca/Fe)-LDH nanoparticles in the manufactured beads interacted with polluted water confirming that the nanoparticles own the prospective for acting as a latent sorbent to remove contaminants from aquatic media.